The role of CXCL12/CXCR4/CXCR7 axis in cognitive impairment associated with neurodegenerative diseases - Rojin Sarallah; Shima Jahani; Alireza Soltani Khaboushan; Amir Kian Moaveni; Maryam Amiri; Masoumeh Majidi Zolbin (Brain, Behavior, & Immunity - Health)
Neurodegenerative diseases, including Alzheimer's Disease (AD), Parkinson's Disease (PD), Multiple Sclerosis (MS), and Amyotrophic Lateral Sclerosis (ALS), are characterized by progressive neuronal loss and cognitive impairment (CI). The: Cysteine-X-cysteine chemokine ligand 12(CXCL12)/CXC chemokine receptor type 4 (CXCR4)/CXC chemokine receptor type 7 (CXCR7) axis has emerged as a critical molecular pathway in the development of CI in these disorders. This review explores the role of this axis in the pathogenesis of CI across these neurodegenerative diseases, synthesizing current evidence and its implications for targeted therapies. In AD, dysregulation of this axis contributes to amyloid-β accumulation and tau hyperphosphorylation, leading to synaptic dysfunction and cognitive decline. PD studies reveal that CXCL12/CXCR4 signaling influences dopaminergic neuron survival and microglial activation, affecting cognitive function. In MS, the axis modulates neuroinflammation and demyelination processes, impacting cognitive performance. ALS research indicates that the CXCL12/CXCR4/CXCR7 pathway is involved in motor neuron degeneration and associated cognitive deficits. Across these diseases, the axis influences neuroinflammation, synaptic plasticity, and neuronal survival through various signaling cascades, including PI3K/AKT, MAPK, and JAK/STAT pathways. Emerging evidence suggests that modulating this axis could provide neuroprotective effects and potentially alleviate cognitive symptoms. This review highlights the potential of the CXCL12/CXCR4/CXCR7 axis as a therapeutic target for addressing CI in neurodegenerative diseases. It also underscores the need for further research to fully elucidate its role and develop effective interventions, potentially leading to improved clinical management strategies for these devastating disorders.